Informal Employment in Argentina : Causes and Consequences - World Bank (Washington, DC, 2012)
This report presents the final results and conclusions of a two-year program developed by a World Bank team in Argentina, to analyze the determinants of informality and its impact on poverty and equity. Informality in the labor market has become a central concern for policy makers and the society at large in Argentina. The long upward trend in informal employment until recent year has been viewed as a deterioration in working conditions that is behind the sustained rise in poverty and inequality in the last quarter of the twentieth century. While some of the possible causes for the rise in informality have been studied, their relative importance remains unclear and its links with poverty and inequality have not been examined in detail. A primary objective of the program is to deepen the shared work with the Argentine government and civil society on socio-economic development and equity issues. The aim has been to analyze and propose policy options for the labor market that respond to the Government's priorities, are technically sound, and provide an open menu for discussion. The study of informality in the labor market is not an empty field in Argentina. Many local analysts have studied its causes and consequences, and this report built on this work. A key aspect of the program was to draw on the extensive local analytical studies on the issues and sustain an active interaction with government counterparts and civil society through technical workshops, meetings and other outreach efforts. This report focused on discussing the evolution, determinants, and policy options to reduce labor informality in Argentina and its impacts. By developing a common base of diagnoses with the government, the program set a path for further discussions and collaborations. Following this process, the Ministry of Labor has already asked the Bank to collaborate on a new program that will focus on labor markets, social protection, and income distribution, looking for policies that would result in better and more effective policies to increase equity in Argentina.